Categories of Speech Functions Used by Totto-Chan and Mr. Kobayashi in Totto-Chan: The Little Girl at the Window - Napitupulu, Esther Febriana Tiurmaida; Bram, Barli (Center of Language and Cultural Studies [CLCS], 2021)
This research aimed at analyzing the categories of speech functions used by the characters Totto-Chan and Mr. Kobayashi in Totto-Chan: The Little Girl at the Window book. There are two research questions, namely, 1) what categories of speech functions are used by Totto-chan and Mr. Kobayashi in Totto-Chan: The Little Girl at the Window? and 2) which categories of speech functions are dominantly used by Totto-chan and Mr. Kobayashi in Totto-Chan: The Little Girl at the Window? The researcher used qualitative research method and content analysis. In analyzing and categorizing the data, the researcher used Holmes’ & Wilson’s (2017) speech function theory and two other functions of speech by Searle (1979). According to the research results, Totto-chan uses seven categories of speech functions, namely, expressive, directive, referential, metalinguistic, poetic, phatic, and commissive functions. Whereas, Mr. Kobayashi uses seven categories of speech functions. They are expressive, directive, referential, poetic, phatic, commissive, and performative functions. the categories of speech functions that are dominantly used by Totto-chan are referential, expressive, and phatic functions. Whereas, the categories of speech functions that are dominantly used by Mr. Kobayashi are referential, phatic, and imperative functions, which are included in directive functions.